Establishment of a Heterologous RNA Editing Event in Chloroplasts . Issue 3 (13th September 2019) - Loiacono, Filomena Vanessa; Thiele, Wolfram; Schöttler, Mark Aurel; Tillich, Michael; Bock, Ralph
Abstract : An Arabidopsis PPR protein fully edits a heterologous editing site from spinach in tobacco chloroplasts. Abstract: In chloroplasts and plant mitochondria, specific cytidines in mRNAs are posttranscriptionally converted to uridines by RNA editing. Editing sites are recognized by nucleus-encoded RNA-binding proteins of the pentatricopeptide repeat (PPR) family, which bind upstream of the editing site in a sequence-specific manner and direct the editing activity to the target position. Editing sites have been lost many times during evolution by C-to-T mutations. Loss of an editing site is thought to be accompanied by loss or degeneration of its cognate PPR protein. Consequently, foreign editing sites are usually not recognized when introduced into species lacking the site. Previously, the spinach ( Spinacia oleracea ) psbF -26 editing site was introduced into the tobacco ( Nicotiana tabacum ) plastid genome. Tobacco lacks the psbF -26 site and cannot edit it. Expression of the "unedited" PsbF protein resulted in impaired PSII function. In Arabidopsis ( Arabidopsis thaliana ), the PPR protein LPA66 is required for editing at psbF -26. Here, we show that introduction of the Arabidopsis LPA66 reconstitutes editing of the spinach psbF -26 site in tobacco and restores a wild-type-like phenotype. Our findings define the minimum requirements for establishing new RNA editing sites and suggest that the evolutionary dynamics of editing patterns is largely explained by coevolution of editing sites and PPR proteins.